2016
DOI: 10.1016/j.jshs.2014.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an active educational video game on children's motivation, science knowledge, and physical activity

Abstract: BackgroundActive educational video games (AVGs) appear to have a positive effect on elementary school students' motivation leading to enhanced learning outcomes. The purpose of this study was to identify the effectiveness of an AVG on elementary school students' science knowledge learning, physical activity (PA) level, and interest-based motivation.MethodsIn this randomized controlled study, 53 elementary school students were assigned to an experimental condition or a comparison condition. The experimental con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 34 publications
(44 reference statements)
2
20
0
9
Order By: Relevance
“…There were no studies of high school students. Three trials randomized individual students to the intervention or control condition [3032]. In the remaining trials randomization was completed at the level of the cluster; the unit of randomization was the school in 6 trials [28,3337] and the classroom in 16 trials [20,3851].…”
Section: Resultsmentioning
confidence: 99%
“…There were no studies of high school students. Three trials randomized individual students to the intervention or control condition [3032]. In the remaining trials randomization was completed at the level of the cluster; the unit of randomization was the school in 6 trials [28,3337] and the classroom in 16 trials [20,3851].…”
Section: Resultsmentioning
confidence: 99%
“…The results clearly demonstrated a higher situational interest from the exergaming unit than that from the conventional fitness unit. In another study on the relationship between situational interest and an active-game based science unit, Sun and Gao (2016) provided evidence showing low to moderate correlation between situational interest dimensions and physical activity levels measured by heart rate (r ranged from .12 to .44). This finding indicates that when the activities are derived from a classroom-based content (i.e., science), the relationship might become unstable.…”
Section: Motivational Effect Of Situational Interestmentioning
confidence: 99%
“…Exergames have been gradually implemented in rehabilitation [ 37 , 38 ], education [ 39 ], and other fields [ 40 ], and have been widely accepted by a range of populations from children [ 41 , 42 ] to the elderly [ 43 , 44 ]; moreover, positive results were found for individuals with various diseases such as dementia [ 45 ], stroke [ 46 ], Parkinson disease [ 34 ], multiple sclerosis [ 47 ], cystic fibrosis [ 48 ], and cancer [ 49 ]. Recent studies have demonstrated the feasibility, acceptability, and effectiveness of exergaming in improving physical functions such as gait and balance [ 50 ], motion control [ 51 ], and exercise capacity [ 52 ].…”
Section: Introductionmentioning
confidence: 99%